Famished : eating disorders and failed care in America - Lester, Rebecca J., 1969- (University of California Press, 2019)
"When Rebecca Lester was eleven years old--and again when she was eighteen--she almost died from anorexia nervosa. Now both a tenured professor in anthropology and a licensed social worker, she turns her ethnographic and clinical gaze to the world of eating disorders--their history, diagnosis, lived realities, treatment, and place in the American cultural imagination. Famished is the culmination of over two decades of anthropological and clinical work--as well as a lifetime of lived experience--that presents a profound rethinking of eating disorders and how to treat them. Through a mix of rich cultural analysis, detailed therapeutic accounts, and raw autobiographical reflections, Famished helps make sense of why people develop eating disorders, what the process of recovery is like, and why treatments so often fail. It's also an unsparing condemnation of the tension between profit and care in the American healthcare scheme, demonstrating how a system set up to treat a disease may, in fact, perpetuate it. Fierce and vulnerable, critical and hopeful, Famished will forever change the way you understand eating disorders and the people who suffer with them"--Provided by publisher.